DARE Newsletter, Vol. 5, Nos. 2/3, Spring/Summer 2002 - DARE; Simon, David; Witherell, Elizabeth H. (Dictionary of American Regional English, 2002)
Contents: "From DARE to Henry David Thoreau" by Elizabeth H. Witherell; "Volume IV Is in Press!"; "Funding Update" by David Simon; "Volume IV DARE Quiz"; "Ask a Fieldworker: August Rubrecht, Patt VanDyke"; "Notes and Quotes"
Quarterly newsletter of the Dictionary of American Regional English
Keywords: Americanisms; Dictionaries; Fieldwork; Lexicography; English Language--Dialects--United States; Regional English